Foundations of geomagnetism - Backus, George; Parker, Robert 1942-; Constable, Catherine, 1958- (Cambridge ; New York : Cambridge University Press, 2005)
The main field -- Classical electrodynamics -- Spherical harmonics -- Gauss' theory of the main field -- The mie representation -- Hydromagnetics of the core -- Mathematical background.
Originalmente publicado en 1996
Keywords: Magnetismo terrestre; Hidrodinámica; Procesos de Gauss; Geomagnetismo